PERAN BUDAYA LITERASI DALAM MENINGKATKAN KETERAMPILAN MEMBACA SISWA DI SD NEGERI 25/III DESA JUJUN - Nababil, Mahesa; Muspawi, Mohammad; Rahman, K.a (STKIP Pesisir Selatan, 2024)
Literacy culture is an important element in developing students' reading skills, especially at the primary school level. GLS emphasizes the importance of literacy activities before starting lessons, by inviting students to read for 15 minutes at the beginning of the school day. In addition, schools are also encouraged to provide a variety of reading materials that are interesting and relevant to students' needs, so as to trigger their interest in reading. This research was conducted at SD Negeri 25/III Jujun Village by using the subject of all students at SD Negeri 25/III Jujun Village. The approach used in this research is qualitative research. The results of observations show that students' reading skills still need improvement, especially in terms of reading comprehension. The literacy program at school, such as the 15-minute reading activity every day, has had a positive impact, but obstacles such as limited interesting reading materials and the lack of library facilities are still an obstacle. This study highlights that support from teachers, parents and wider access to varied reading materials are crucial in building an effective literacy culture. The study concludes that collaboration between schools, families and communities is needed to create a conducive literacy environment to holistically improve students' reading skills.